Phytochemical Profiling, Anti-inflammatory, Antioxidant and Antimicrobial Effects of Seven Indian Morinda Species - Singh, Bharat; Sahu, Pooran; Sharma, Ram (Current Bioactive Compounds, 2022)
Background: The fruits, leaves and roots of Morinda species are used in the treatment of inflammations, cancers, diabetes, psychiatric disorders, bacterial and viral infections. However, no study has been conducted on chemical profiling, anti-inflammatory, antioxidant and antimicrobial potentials of leaves of seven Indian Morinda species. Aim: The study aimed to investigate the anti-inflammatory, antioxidant and antimicrobial effects of methanol extract of seven Indian Morinda species. Materials and Methods: The total contents of iridoids, flavonoids, anthraquinone glycosides, triterpenoids, lignans and coumarins from methanol extract of each species were determined by using different established protocols. The anti-inflammatory activity of methanol extracts of each species was evaluated using carrageenan and CFA-induced arthritis in male Wistar albino rats. In vivo, antioxidant activity was determined by estimating the levels of superoxide dismutase, catalase, glutathione and malondialdehyde in liver and kidney homogenates of male Wistar rats. The antimicrobial activity of methanol extracts of all seven species was determined by using the microdilution method against selected microbes. Results: Different values of total contents of iridoids, flavonoids, anthraquinone glycosides, triterpenoids, lignans, and coumarins were achieved from methanol extract of leaf of M. umbellata, M. jasminoides, M. reticulata, M. parvifolia and M. persicaefolia. The potent anti-inflammatory effect was demonstrated (carrageenan-induced paw oedema model) by methanol extract of leaves of M. umbellata at 50 mg/kg dose. Similarly, M. umbellata methanol extract showed maximum antiarthritic effect against CFA-induced arthritis on the 17th day (p.o.). Maximum SOD levels in liver and kidney homogenates were increased by the methanol extract of M. persicaefolia. The catalase concentration was enhanced by the methanol extract of M. jasminoides. GSH level was raised by the methanol extract of leaves of M. umbellata, but M. royoc reduced the levels of MDA in treated animals. The methanol extract of M. parvifolia leaves displayed maximum antibacterial activity against K. pneumoniae. M. persicaefolia methanol extract showed the strongest antifungal activity against P. chrysogenum. Conclusion: The methanol extract of leaves of M. jasminoides, M. reticulata, M. parvifolia, M. umbellata and M. persicaefoli showed promising anti-inflammatory, antioxidant and antimicrobial effects on the studied experimental models.
Keywords: morinda species